2014
DOI: 10.1002/qua.24715
|View full text |Cite
|
Sign up to set email alerts
|

Density functional and multiconfigurational ab initio study of the ground and excited states of Os2

Abstract: Multiconfigurational ab initio methods predict that the 5Πu state as the ground state instead of the 7Δu state. Although multiconfigurational perturbation theory correctly predicts the ground state, they overestimate the bond dissociation energy (BDE). Only multireference configuration interaction method can reasonably calculate the BDE. The spin‐orbit effect on the spectroscopic constants is not significant. The results calculated by density functional theory (DFT) vary significantly depending on the selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(67 reference statements)
2
8
1
Order By: Relevance
“…For Hf 2 , the revTPSS/SDD scheme gives 6 μ B for the GS, which is different from the experimental value and revTPSS/TZP value of 2 μ B . Previous studies reported the disagreement in the magnetic moment of Os 2 with values of 4 μ B or 6 μ B for the lowest energy structures. , We also found that the revTPSS/SDD and revTPSS/TZP methods give different magnetic moments for Os 2 dimer with values of 6 μ B and 4 μ B , respectively.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…For Hf 2 , the revTPSS/SDD scheme gives 6 μ B for the GS, which is different from the experimental value and revTPSS/TZP value of 2 μ B . Previous studies reported the disagreement in the magnetic moment of Os 2 with values of 4 μ B or 6 μ B for the lowest energy structures. , We also found that the revTPSS/SDD and revTPSS/TZP methods give different magnetic moments for Os 2 dimer with values of 6 μ B and 4 μ B , respectively.…”
Section: Resultscontrasting
confidence: 76%
“…The rows starting with δ and δ̅ represent the average and overall average error between theoretical and experimental data, respectively. The van der Waals species (Zn 2 , Cd 2 , Hg 2 ) are not discussed in this work because there are all covalent or ionic interactions in M@Au 12 clusters. b Reference . c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . k Reference . l Reference . m Reference . n Reference . o Reference . p Reference . …”
Section: Resultsmentioning
confidence: 99%
“…eV, respectively. 55 Considering the difficulty of the problem (the wide range of previous results) and the uncertainty in the experimental results, the tPBE and ftPBE results are both considered satisfactory.…”
Section: Cumentioning
confidence: 94%
“…PBE overestimates the Compared to other transition metal dimers, there are fewer theoretical studies on Os 2 . Due to its multiconfigurational character, the predictions depend strongly on the choice of functional and basis set, with the calculated ground state being either 7 Δ u or a 5 Π u [52][53][54][55]. In addition to a KS-DFT study, Kim et al55 reported CASSCF, CASPT2, MRMP2, and MRCI wave function results…”
mentioning
confidence: 97%
“…So, theoretical studies shed light onto studying different characteristics of the system with expense of computation time [6]. Nowadays, improvements in computer technology and DFT made theoretical In nanoscale, surface morphology of materials shows different characteristics compared to bulk size [9].The particle size of biomaterials used in the field of dentistry is decreased to below 100nm [10].…”
Section: Introductionmentioning
confidence: 99%